Biomedical ethics - O'Neill, Terry, 1944- (San Diego, Calif. : Greenhaven Press, 1952)
Presents opposing viewpoints on various issues of biomedical ethics, including animal testing, human testing, organ transplants, genetic testing, gene therapy, and cloning.
Includes bibliographical references (p. [128]-140) and index.
Keywords: Medical ethics -- Juvenile literature; Bioethics -- Juvenile literature; Medical ethics; Bioethics